52.4k views
5 votes
Solve for 2. Enter the solutions from least to greatest.(x + 6)2 – 16 = 0lesser 1 =greater I =

1 Answer

2 votes

The given expression is


(x+6)^2-16=0

First, we add 16 on each side


\begin{gathered} (x+6)^2-16+16=16 \\ (x+6)^2=16 \end{gathered}

Then, we apply a square root on each side


\begin{gathered} \sqrt[]{(x+6)^2}=\sqrt[]{16} \\ x+6=\pm4 \end{gathered}

Now, we subtract 6 from each side


\begin{gathered} x+6-6=\pm4-6 \\ x_1=4-6=-2 \\ x_2=-4-6=-10 \end{gathered}Therefore, the lesser solution is -10 and the greater solution is -2.
User Helle
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.